(untitled) (Research, Society and Development, 2022)
The COVID 19 pandemic triggered rapid transformations in health care and expressed the weaknesses present in the relationships of care organizations. Considering the increase in demand and the consequent drop in the supply of medicines in the pandemic period, there is a need to use tools that help health centers in the management of their stocks. Therefore, Pareto’s ABC curve presents itself as a fundamental tool, based on the importance of the items, quantities used and their values. This article aims to demonstrate the application of the ABC curve for medication management in a hospital pharmacy of a private hospital located in a city in the countryside of Bahia. Three Pareto ABC curves were prepared considering data from the years 2019, 2020 and 2021 so that previous and current data from the pandemic were used. It was possible to notice that there was variation, especially among the items of Class A, since during the pandemic, muscle relaxants, anesthetics and sedatives that make up the so-called "intubation kit" and drugs to combat pulmonary infections were among the highest percentage costs of the pharmacy hospital, still representing a great impact on the stock with high proportions of SKU (Stock Keeping Unit). A significant increase in the value of certain medications was also notable, which directly impacted the total annual cost of medication in the hospital pharmacy. It was then possible to affirm that the pandemic caused financial impacts on the hospital’s CAF, and that such effects could be minimized with the adoption of the administrative methods presented.